2020
DOI: 10.22270/jddt.v10i4.4261
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial, Antiviral and Cytotoxicity Activities of Aspergillus oryzae Isolated From El-Baida Marsh in Algeria

Abstract: This work covers the study of antimicrobial and antiviral activities of the Aspergillus oryzae strain isolated from saline soil (El-Baida marsh in Algeria). The crude extract obtained with ethyl acetate displayed antimicrobial activity against Gram-positive and Gram-negative bacteria and the yeast Candida albicans with a mean of 16.69 mm of inhibition zone and a minimal inhibitory concentrations MICs between 7.28 and 21.85 μgmL-1. We also assessed the antiviral activity against Herpes simplex-2 Virus (HSV-2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…As shown in Table 1, the promising compounds for 3CLpro-CoV2 or PLpro-CoV2 inhibitors are dominated from Aspergillus groups. Antiviral activity of Aspergillus groups against some viruses are widely reported [102][103][104][105], nevertheless no report for experimental evidence on the antiviral properties of this group against living SARS-CoV-2 exists. Interestingly, Koehler et al [106] reported that COVID-19 patients are more susceptible towards invasive pulmonary aspergillosis (IPA).…”
Section: Microorganisms As Sources Of Inhibitors Targeting Sars-cov2 Proteasesmentioning
confidence: 99%
“…As shown in Table 1, the promising compounds for 3CLpro-CoV2 or PLpro-CoV2 inhibitors are dominated from Aspergillus groups. Antiviral activity of Aspergillus groups against some viruses are widely reported [102][103][104][105], nevertheless no report for experimental evidence on the antiviral properties of this group against living SARS-CoV-2 exists. Interestingly, Koehler et al [106] reported that COVID-19 patients are more susceptible towards invasive pulmonary aspergillosis (IPA).…”
Section: Microorganisms As Sources Of Inhibitors Targeting Sars-cov2 Proteasesmentioning
confidence: 99%